The Functional Free Innervated Medial Gastrocnemius Flap - Grinsell, Damien; Yue, Brian Yin Ting (Journal of Reconstructive Microsurgery, 2014)
Background The functional free innervated medial gastrocnemius flap has been described in four previous articles for the management of foot drop, Volkmann contracture, and upper limb muscle defects. We expand the indications by describing the use of free innervated medial gastrocnemius musculocutaneous flap in functional reconstruction of the tongue and upper limb musculature.Methods The right medial gastrocnemius muscles were raised as myocutaneous flaps in six patients. These flaps were elevated in the supine position and the flaps included a motor nerve from the sciatic nerve and a sensory nerve from the sural nerve. The average size of flap was 15 × 8 cm.Results The flaps were transferred successfully with no flap loss and showed consistent reinnervation during follow-up. In particular, all patients who underwent tongue reconstruction exhibited intelligible speech and returned to full oral diet with no aspiration. In patients who underwent upper limb muscle reconstructions, there was moderate to full restoration of power. All donor sites exhibited excellent symmetry in both power and appearance to the contralateral calf.Conclusions To our knowledge, this study is the first to describe the use of the innervated medial gastrocnemius free flap in the reconstruction of the tongue and deltoid. The advantages of this flap include its thin reliable skin paddle, strong bulky bipennate muscle, and low donor site morbidity.
Keywords: medial gastrocnemius; musculocutaneous; tongue reconstruction